Strategi Komunikasi: Reintegrasi Sosial Anak Berhadapan Hukum di Kabupaten Nunukan - Yusmanizar; Andi Vita Sukmarini; Aiyub (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Social issues involving children in conflict with the law in Indonesia, particularly in Nunukan Regency, are increasingly complex. The Ministry of Social Affairs, focusing on such cases, indicates a rise in sexual abuse cases against underage girls. Research conducted at the Social Services, Women's Empowerment, and Child Protection Agency of Nunukan Regency underscores the importance of family communication, affection, and attention in supporting social reintegration of these children. Effective communication is noted as key in this process, despite obstacles such as resource limitations. PT Pos Indonesia, facing dynamic consumer demands, is turning to strategic innovations and digital economy. Adapting to changes in business environment and consumer needs, the company is modernizing its services, investing in technology infrastructure, and shifting from profit-oriented to customer-oriented paradigms. Despite challenges, PT Pos Indonesia is committed to fostering an adaptive and innovative organizational culture, and leveraging technology to overcome supply chain obstacles and increase efficiency.